2021
DOI: 10.1053/j.ajkd.2021.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Variants in the Genes Affected in Alport Syndrome (COL4A3–COL4A5) and Their Association With Other Kidney Conditions: A Review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 87 publications
1
24
0
1
Order By: Relevance
“…48,49 IgA glomerulonephritis and heterozygous pathogenic variants occur together too often to be coincidental and the thinned GBM may facilitate glomerular immune complex deposition. 50 Inappropriateness of "AD Alport Syndrome" as a Diagnosis These observations that pathogenic heterozygous COL4A3 or COL4A4 variants are uncommonly associated with ESKF, hearing loss, and ocular abnormalities suggest that the term "AD Alport syndrome" itself is not appropriate since 'syndrome' implies the presence of extra-renal features.…”
Section: Explanation Of the Reduced Risk Of Eskf And Extra-renal Feat...mentioning
confidence: 99%
“…48,49 IgA glomerulonephritis and heterozygous pathogenic variants occur together too often to be coincidental and the thinned GBM may facilitate glomerular immune complex deposition. 50 Inappropriateness of "AD Alport Syndrome" as a Diagnosis These observations that pathogenic heterozygous COL4A3 or COL4A4 variants are uncommonly associated with ESKF, hearing loss, and ocular abnormalities suggest that the term "AD Alport syndrome" itself is not appropriate since 'syndrome' implies the presence of extra-renal features.…”
Section: Explanation Of the Reduced Risk Of Eskf And Extra-renal Feat...mentioning
confidence: 99%
“…Recently JS and Philip Harrak reported that how often both diseases occur together is unknown because few individuals with IgA glomerulonephritis routinely undergo electron microscopy for GBM thinning or testing for genetic variants. On the other hand, heterozygous COL4A3 and COL4A4 variants and IgA disease each affect ~1% of the population, so the conditions might coexist by chance in 0.01% [ 38 ]. Kohei Omachi (Washington University, St. Louis, USA), from the group of Jeff H. Miner, reported on ways to detect and assess the pathogenicity of novel variants, having established a collagen alpha 345(IV) heterotrimer formation assay that is amenable to high throughput screening by using a split NanoLuc luciferase complementarity system [ 39 ].…”
Section: What To Do When Alport Syndrome Is Strongly Suspected But a ...mentioning
confidence: 99%
“…Although there are isolated reports of complement pathway risk alleles in IgA glomerulonephritis, the only major ones are ITGAM and ITGAX that code for integrins that facilitate complement-dependent phagocyte activation and immune complex clearance. Interestingly both IgA glomerulonephritis and retinal drusen are also associated with variants in COL4A3 or COL4A4 , and GBM thinning that may facilitate IgA movement into the mesangium 43 .…”
Section: Discussionmentioning
confidence: 99%